Applying of thin plate boundary condition in analysis of ship's magnetic field. Issue 5 (24th August 2018) - Jankowski, Piotr; Woloszyn, Miroslaw
Abstract : Purpose: The purpose of this paper is to present computer simulations of ship's magnetic signatures using a new thin plate boundary condition implemented in the Opera 3D 18R2 programme. This paper aims to check the magnetic signatures' numerical calculations precision of objects using the thin plate boundary conditions and analysis of the magnetic signature of ship with a degaussing system and with and without inner devices. Design/methodology/approach: The ferromagnetic sphere and cube with and without the thin plate boundary condition were compared. The computer results of the magnetic field of a sphere were compared with an analytical solution. A superstructure, decks, hull and bulkheads of a corvette were modeled. An analysis of ship's magnetic field with consideration of inner ferromagnetic devices and with degaussing system was carried out. Findings: The results of the analytical and numerical comparative analysis of magnetic field of cube and sphere have shown that the thin plate boundary condition is a good method for analysis of magnetic signatures of thin-walled objects. The computer simulations of the corvette model have shown that for relative magnetic permeability of a few hundred range the influence of inner ferromagnetic devices on the ship's magnetic signature is negligible. The thin plate boundary condition is also good method for calculation of the ship magnetic signature with degaussing system and for optimization currents of coils. Originality/value: The calculation time of ship's magnetic field with the thin plate boundary condition bears resemblance to the ship model with layers of steel.